2018
DOI: 10.1590/0074-02760170083
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a rare, reassortant human G10P[14] rotavirus strain detected in Honduras

Abstract: BACKGROUNDAlthough first detected in animals, the rare rotavirus strain G10P[14] has been sporadically detected in humans in Slovenia, Thailand, United Kingdom and Australia among other countries. Earlier studies suggest that the strains found in humans resulted from interspecies transmission and reassortment between human and bovine rotavirus strains.OBJECTIVESIn this study, a G10P[14] rotavirus genotype detected in a human stool sample in Honduras during the 2010-2011 rotavirus season, from an unvaccinated 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Nevertheless, unusual RVA genotypes have been frequently detected, such as: G3[P6], G12[P6], G8P[4], and G8P[6] and more recently the equine-like G3P[8] [ 17 , 23 , 24 ]. Similarly, recent studies from other countries have reported the detection of rare RVA genotype combination [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 65%
“…Nevertheless, unusual RVA genotypes have been frequently detected, such as: G3[P6], G12[P6], G8P[4], and G8P[6] and more recently the equine-like G3P[8] [ 17 , 23 , 24 ]. Similarly, recent studies from other countries have reported the detection of rare RVA genotype combination [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 65%
“…The frequency of untypable G or P‐genotype specimens was 13.07% and 8.66%, respectively. On one hand, it may be the result of a mismatch between primers and target sequences, as new G and P genotypes appeared in recent years . Some mismatches were observed after alignment of the primers and the VP7 and VP4 sequences of recently appeared genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, it may be the result of a mismatch between primers and target sequences, as new G and P genotypes appeared in recent years. [41][42][43][44][45] Some mismatches were observed after alignment of the primers and the VP7 and VP4 sequences of recently appeared genotypes. The corresponding sequences of these untypable rotavirus strains can be obtained by optimizing primer sequences or by Sequence-Independent-Single-Primer-Amplification for genotyping in the future.…”
Section: Phylogenetic Analysis Included the Vp7 And Vp4 Genes Of G9mentioning
confidence: 99%
“…The frequencies of P types were P [8] (25%) (3/12) and P [4] 8.3% (1/12). Rotavirus types P [1], P [5], P [7], P [9], P [10] and P[11] were not detected throughout the current study (Table 3, Fig. 3).…”
Section: Rotaviruses G and P Typesmentioning
confidence: 77%
“…About 37 P and 27 G rotavirus genotypes have been detected in humans and animals [7]. Only a limited number of GxP[y] genotypes confederations are popular in humans, such as G1P [8], G2P [4], G3P [8], G4P [8], and G9P [8] [7], and unusual combinations such as G8P [4], G12P [8], G3P [9], G10P [8], G10P [14] and G1P [4] have also been reported lately [8][9][10].…”
Section: Introductionmentioning
confidence: 99%